2018
DOI: 10.1021/acsnano.8b00303
|View full text |Cite
|
Sign up to set email alerts
|

Toward Self-Control Systems for Neurogenic Underactive Bladder: A Triboelectric Nanogenerator Sensor Integrated with a Bistable Micro-Actuator

Abstract: Aging, neurologic diseases, and diabetes are a few risk factors that may lead to underactive bladder (UAB) syndrome. Despite all of the serious consequences of UAB, current solutions, the most common being ureteric catheterization, are all accompanied by serious shortcomings. The necessity of multiple catheterizations per day for a physically able patient not only reduces the quality of life with constant discomfort and pain but also can end up causing serious complications. Here, we present a bistable actuato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 56 publications
(94 reference statements)
0
71
0
Order By: Relevance
“…Nanogenerators are promising to address such challenges in ways of serving as self‐powered health sensors or acting as the power source of the self‐powered health sensing system. TENGs have been applied for implantable heath monitors in both ways . Ma et al reported an implantable TENG that can monitor multiple physiological and pathological signs in real time ( Figure a–c) .…”
Section: Implantable Tengs For Health Monitoringmentioning
confidence: 99%
“…Nanogenerators are promising to address such challenges in ways of serving as self‐powered health sensors or acting as the power source of the self‐powered health sensing system. TENGs have been applied for implantable heath monitors in both ways . Ma et al reported an implantable TENG that can monitor multiple physiological and pathological signs in real time ( Figure a–c) .…”
Section: Implantable Tengs For Health Monitoringmentioning
confidence: 99%
“…In addition to aforementioned medical information related to respiration, cardiovascular system, body temperature, and perspiration, the self‐powered sensors based on or powered by energy harvesters were also demonstrated to show capacity in detecting other medical signals deriving from bladder, eye ball, stomach, and brain …”
Section: Self‐powered Sensors For Medical Signals Detectionmentioning
confidence: 99%
“…Increasing surface charge generated by contact electrification is also useful for sensing of human activity such as bodily motion, bending or touching (via sensing of pressure), and physiological signals by wearable or implantable devices . One specific application involves an ultrasensitive pulse sensor based on a flexible TENG (Figure d) .…”
Section: Recent Applications Of Contact Electrificationmentioning
confidence: 99%